Healthy families of children who are deaf. - Luckner JL; Velaski A (American Annals of the Deaf)
Families provide the building blocks for the development of healthy, happy, competent children. The purpose of the present study was to identify and interview healthy families of children who were deaf. The researchers were interested in identifying factors that contribute to families' health as well as in collecting suggestions for other families with children who are deaf and for professionals in the field of deaf education. Nineteen families, all nominated by deaf education professionals, were interviewed. The interviews were transcribed and coded, and responses to each interview question were grouped under recurring themes. A summary of the results, limitations of the study, suggestions for future research, and recommendations for practice are provided.